Desarrollo del área socio afectivo a traves de herramientas tecnológicas en niños de 24 a 36 meses - Cervantes Montaluisa, Johanna Estefanía (2017)
This project has as objective give relations the children learning objectives, orientation exercises and required stimulation during the develop in the area socio affective using technological tools as didactic resources in the learning process to better the use of goals in children between 24 to 36 months in the Children “Escuela del Buen Vivir” in Eloy Alfaro Zone, it is seen the managed of a cuali cuantitative methodology through collected registers in those institutions with built population of 109 children, 208 parents and 7 comunity mothers. This is the reason that we have designed wood a ludo table with polyethylene of high density and profiled in aluminum with dimensions of 90 cm high for 60 length and 55 high. The same that have projected according to the needs, abilities and skills that child has to develop in these ages, with the use of friendly materials to the environment, not toxic and join to understood plans they are going to become in a support that could let as fascilitators as children to better the teaching process helping in the develop social learning of children, as in the Children del Centro del Buen Vivir, saying a lack of didactic and technological materials that encourage children in their learning so the use of technological learning skills form part of the evolution and pedagogical process, because they help of a direct way to the fulfillment of the marked objective in each one of the Children Centre.